Measuring Involvement of a Network of Customers in NPD. Issue 2 (2nd September 2015) - Lynch, Patrick; O'Toole, Thomas; Biemans, Wim
Abstract : The new product development (NPD) literature is rife with suggestions to involve customers in the innovation process, and many firms collaborate with customers. But the extant literature does not offer much guidance concerning the nature and quality of involving such a network of customers. This paper contributes to the extant literature on customer involvement by identifying a comprehensive set of metrics to measure the involvement of a network of customers in NPD. It introduces metrics describing three aspects of customer involvement: (1) the rationale for involving a network of customers in NPD, (2) the network of customers involved in NPD, and (3) the interaction process between manufacturer and customers at the level of individual customers. These metrics help to understand the roles of customers, the timing of their involvement at each stage in the development process, the type and number of customers that are involved, as well as the frequency and intensity of their involvement. The use of these metrics is illustrated by a study of customer network involvement by Irish business‐to‐business companies. Forty‐six percent of the sampled firms ( n  = 1400) were actively involved in NPD, but very few of them involved customers in the early stages ( n  = 77). The involvement of customers in early NPD stages is significant, although manufacturers tend to go back to the same customers repeatedly. The intensity of customer involvement is also extensive, but even more so during the later NPD stages, especially for new products as opposed to product improvements. By incorporating a network perspective, the proposed metrics for customer network involvement provide a new approach for researchers to study the involvement of customers in NPD.